Building Pesantren Independence Through Innovation in Pesantren Cooperatives - Siregar, Erpiana; Harahap, Titi Martini; Siregar, Resi Atna Sari (Al-Fikru: Jurnal Ilmiah, 2025)
This research departs from the challenges of modernization that affect the moral and spiritual values of the younger generation, including in the context of Islamic education. Pesantren, as educational institutions that have an important role in shaping the character of santri, face the need to become economically independent so as not to depend on government assistance. The purpose of this study is to analyze the model of pesantren economic independence through the management of pesantren cooperatives, as well as how these cooperatives can support the economic empowerment of pesantren and the surrounding community. This research uses a descriptive qualitative approach with data collection methods through interviews, observation, and documentation. The results showed that Al-Abraar Islamic Boarding School succeeded in developing several effective cooperative business units, such as oil palm plantations and animal husbandry, to support its economic independence. On the other hand, Musthafawiyah Islamic Boarding School faces obstacles in cooperative management due to limited licensing and management quality. The implication of this study is the importance of strengthening the managerial capacity and governance of cooperatives to achieve sustainable economic independence of pesantren.